Leakage during seed imbibition - Simon, E. W.; Raja Harun, Raja Muhammad (Oxford University Press, 1972)
When pea embryos are placed in water solutes leak from them at a ruto which declines rapidly at first and then more slowly. Embryos can be dried down over calcium chloride and will then leak as before when returned to water. Similar results were obtained with Ricinus seeds after removal of the testa. Pea embryos that have first been allowed to imbibe some water through a small part of their surface (by placing them on damp filter-paper) leak relatively slowly when subsequently immersed in water; the greater the initial imbibition the slower tho subsequent leakage. Likewise, embryos taken from peas that were harvested when succulent and tender show only show Ieakage. It is proposed that as seeds dry out in the course of dovelopment cell membranes lose their integrity. . Whon such dry seeds are allowed to imbibe water there is a short. period, Before membrane integrit.y is re-established, during which solutes can leak out of the cells.